Advances in the Role of Endothelial Cells in Cerebral Small Vessel Disease - Bai, Tao; Yu, Shijia; Feng, Juan (Frontiers in Neurology, 2022)
Cerebral small vessel disease (CSVD) poses a serious socio-economic burden due to its high prevalence and severe impact on the quality of life of elderly patients. Pathological changes in CSVD mainly influence small cerebral arteries, microarteries, capillaries, and small veins, which are usually caused by multiple vascular risk factors. CSVD is often identified on brain magnetic resonance imaging (MRI) by recent small subcortical infarcts, white matter hyperintensities, lacune, cerebral microbleeds (CMBs), enlarged perivascular spaces (ePVSs), and brain atrophy. Endothelial cell (EC) dysfunction is earlier than clinical symptoms. Immune activation, inflammation, and oxidative stress may be potential mechanisms of EC injury. ECs of the blood–brain–barrier (BBB) are the most important part of the neurovascular unit (NVU) that ensures constant blood flow to the brain. Impaired cerebral vascular autoregulation and disrupted BBB cause cumulative brain damage. This review will focus on the role of EC injury in CSVD. Furthermore, several specific biomarkers will be discussed, which may be useful for us to assess the endothelial dysfunction and explore new therapeutic directions.